Asynchronous automated electronic laboratory result notifications: a systematic review. (18th May 2017) - Slovis, Benjamin H; Nahass, Thomas A; Salmasian, Hojjat; Kuperman, Gilad; Vawdrey, David K
Abstract: Objective: To systematically review the literature pertaining to asynchronous automated electronic notifications of laboratory results to clinicians. Methods: PubMed, Web of Science, and the Cochrane Collaboration were queried for studies pertaining to automated electronic notifications of laboratory results. A title review was performed on the primary results, with a further abstract review and full review to produce the final set of included articles. Results: The full review included 34 articles, representing 19 institutions. Of these, 19 reported implementation and design of systems, 11 reported quasi-experimental studies, 3 reported a randomized controlled trial, and 1 was a meta-analysis. Twenty-seven articles included alerts of critical results, while 5 focused on urgent notifications and 2 on elective notifications. There was considerable variability in clinical setting, system implementation, and results presented. Conclusion: Several asynchronous automated electronic notification systems for laboratory results have been evaluated, most from >10 years ago. Further research on the effect of notifications on clinicians as well as the use of modern electronic health records and new methods of notification is warranted to determine their effects on workflow and clinical outcomes.